Breast-fed infants and their later cardiovascular health: a prospective study from birth to age 32 years. Issue 6 (8th November 2013) - Pirilä, Satu; Taskinen, Mervi; Viljakainen, Heli; Mäkitie, Outi; Kajosaari, Merja; Saarinen-Pihkala, Ulla M.; Turanlahti, Maila
Abstract : The aim of the present study was to evaluate the impact of infant breast-feeding on cardiovascular risk in young adults. This unique study group involved 158 subjects (eighty-two females) originally collected prospectively at birth in 1975 and followed up to the age of 32 years. Frequent visits during the first year guaranteed the knowledge of the precise duration of breast-feeding. All infants received at least some breast milk. Participants were assessed for both individual cardiovascular risk factors (blood pressure, plasma lipids, homeostatic model assessment of insulin resistance and waist circumference) and the general clinical risk of cardiovascular events by calculating the Framingham risk score (FRS) and the metabolic syndrome criteria score (NCEP-ATPIII; National Cholesterol Education Program's Adult Treatment Panel III). Data on lifestyle factors were carefully collected. Linear regression analyses revealed that the effect of the duration of breast-feeding was not relevant (0·02 decrease in the FRS per one additional breast-feeding month; 95 % CI − 0·19, 0·09). Similarly, the effect of breast-feeding was minor on all of the individual cardiovascular risk factors. We used sex, physical activity, dietary fat and vitamin C, smoking and alcohol consumption as covariates. Again, logistic regression analyses detected no significant impact of the duration of breast-feeding on the risk of the metabolic syndrome according to the NCEP-ATPIII (OR 0·95, 95 % CI 0·8, 1·1). The strongest independent predictor for later CVD risk was male sex. In conclusion, in this prospectively followed cohort of young adults born at term and at weight appropriate for gestational age, the duration of breast-feeding did not have an impact on the accumulation of cardiovascular risk factors.